Enabling multi-electron reaction of ε-VOPO4 to reach theoretical capacity for lithium-ion batteries. Issue 56 (27th June 2018) - Siu, Carrie; Seymour, Ieuan D.; Britto, Sylvia; Zhang, Hanlei; Rana, Jatinkumar; Feng, Jun; Omenya, Fredrick O.; Zhou, Hui; Chernova, Natasha A.; Zhou, Guangwen; Grey, Clare P.; Piper, Louis F. J.; et al.
Abstract : Synthesizing highly crystalline nano-sized ε-VOPO4 particles is the key to achieve theoretical capacity of 2 Li + intercalation in lithium-ion batteries. Abstract : By controlling the morphology and particle size of the epsilon polymorph of vanadyl phosphate, ε-VOPO4, it can fully reversibly intercalate two Li-ions and reach the theoretical capacity of 305 mA h g −1 over two voltage plateaus at about 4.0 and 2.5 V.